PROFESIONAL AUDIT DAN ETIKA KERJA TERHADAP TINDAKAN WHISTLEBLOWING - Magfiroh, Siti; Sunarmo, Agus; Primasari, Dona (Jurnal Analisis Bisnis Ekonomi, 2018)
The long-term goal of this research is to contribute to the theory and be a material consideration and policy for management in quality human resources and develop various strategies that are able to develop factors that influence whistleblowing actions and for the development of accounting science in the auditing field. Data collection in this study was carried out by distributing questionnaires through distribution or direct delivery to internal auditors in the banking industry who were respondents in Banyumas Regency which was also a population. This study aims to examine the antecedents consisting of professional auditors and work ethics that influence the act of carrying out auditors' whistleblowing. The sampling technique in this study using the census technique. While for data analysis using Statistical Product and Service Solution (SPSS) version 25.00 with multiple linear regression programs. The results of the study show that acceptance of the proposed hypothesis is that the auditor's professional variables and work ethics are proven to influence the actions of conducting auditors' whistleblowing.